Disabilities of the arms, pinch strength, and mild cognitive impairment in patients with coronary artery disease. Issue 3 (March 2021) - Ishihara, Kodai; Izawa, Kazuhiro P.; Kitamura, Masahiro; Ogawa, Masato; Shimogai, Takayuki; Kanejima, Yuji; Morisawa, Tomoyuki; Shimizu, Ikki
Highlights: We revealed relation between difficulty in using the arms and mild cognitive impairment (MCI) in coronary artery disease (CAD) patients. The Disability of the Arm, Shoulder, and Hand (DASH) score was higher in CAD patients with MCI. The DASH score was independently associated with MCI. Manual and cognitive function were independently associated with the DASH score. Manual function and activities using the arms could be targets for intervention. Abstract: Background: We aimed to examine the relationship between the difficulty of activity using the arms and mild cognitive impairment (MCI), the relationship between the difficulty of activity using the arms and manual function, and cognitive function in patients with coronary artery disease (CAD). Methods: We conducted a cross-sectional study of 263 non-dementia patients who met the study criteria from 2328 CAD patients. MCI was estimated with the Japanese version of the Montreal Cognitive Assessment (MoCA-J). The difficulty of activity using the arms was evaluated using the Disability of the Arm, Shoulder, Disability of the Arm, Shoulder and Hand and Hand (DASH) questionnaire. Manual function was evaluated by pinch strength and handgrip strength. Results: Age (odds ratio, 1.10), three-fingered pinch strength (odds ratio, 0.69), and DASH score (odds ratio, 1.03) were independently associated with MCI in the multivariable logistic regression analysis. Hemoglobin ( β  = −0.15), handgrip strength ( β  = −0.37), and MoCA-J score ( β  = −0.15) were independently associated with DASH score (Model 1: p  < 0.001, adjusted R 2  = 0.33); hemoglobin ( β  = −0.17), eGFR ( β  = −0.14), three-fingered pinch strength ( β  = −0.25), and MoCA-J score ( β  = −0.14) were independently associated with DASH score in the multivariate regression analysis (Model 2: p  < 0.001, adjusted R 2  = 0.31). Conclusions: The difficulty of activity using the arms was independently associated with manual and cognitive function and MCI in CAD patients.